Using agile practice under the CD-ERP model: A hybrid approach - Almigheerbi, Tereq Salahi; Ramsey, David; Lamek, Anna (Wykorzystanie zwinnych praktyk w modelu CD-ERP: podejście hybrydowe, 2020)
This paper examines the applicability of agile practice in the Collaboratively-Developed Enterprise Resource Planning (CD-ERP) Model. This model has been proposed as a solution to develop Information Systems (ISs) for public universities in Libyan Higher Education (LHE) following the community-source paradigm and based on ERP. The study took place between 2016 and 2020. The purpose of the article is to discuss the possible impact and success of implementing agile practice in such an environment, while a hybrid approach involving agile practice and a predictive method was introduced. The risks and challenges associated with adopting the CD-ERP model are discussed using a SWOT analysis. Finally, the lessons learnt, recommendations, and directions for future work are presented
Informatyka Ekonomiczna = Business Informatics, 2020, Nr 3 (57), s. 9-21
Keywords: community source; agile; CD-ERP model; SWOT analysis; strategic system planning; information system; community-source; praktyki zwinne; strategiczne planowanie systemu; system informacyjny